Aggregation-Induced Emission Probe for Specific Turn-On Quantification of Soluble Transferrin Receptor: An Important Disease Marker for Iron Deficiency Anemia and Kidney Diseases - Zhang, Ruoyu (AMERICAN CHEMICAL SOCIETY, 2020)
10.1021/acs.analchem.7b03694